Pengaruh Industri Dan Pendapatan Perkapita Terhadap Penerimaan Pajak Dengan Kualitas Peraturan Sebagai Pemoderasi - Pius Aji Cakra Bagaskara; Suparna Wijaya (PT WIM Solusi Prima, 2023)
This study aims to determine the effect of the industrial sector's contribution to GDP and per capita income on tax revenues moderated by regulatory quality. The data used is data taken from the World Bank Open Data in the period 2002 to 2019, while the objects studied were 37 countries with the lower-middle income economy category. The method used is a quantitative method with multiple linear regression of panel data with a random effect model. The results of this study indicate that simultaneously, all variables have a positive and significant effect on tax revenues. Partially, the industry's contribution to GDP on tax revenues has a significant negative effect, then after being moderated by the quality of regulations it has no effect. Income per capita has a significant positive effect, but after being moderated by the quality of regulations it actually reduces the level of influence. Furthermore, the quality of the regulations themselves has no effect on tax revenues. This can be overcome by improving regulations to provide ease of doing business and ease of obtaining services from the government.